2018
DOI: 10.1007/s10856-018-6139-0
|View full text |Cite
|
Sign up to set email alerts
|

Polymer coatings based on sulfonated-poly-ether-ether-ketone films for implant dentistry applications

Abstract: Poly-ether-ether-ketone (PEEK) is one of the most important biocompatible polymers and its sulfonation has been studied for biomedical applications. The aim of the present study is to produce, to characterize and to assess bioactivity of PEEK coatings with sulfonated PEEK (SPEEK) films. Biomedical grade PEEK (Invibio®, Batch: D0602, grade: NI1) was functionalized using sulfuric acid 98%. SPEEK was dissolved into DMSO or into DMF, both at 10% mass/volume. PEEK bars (N = 18) and cylinders (N = 27) were manufactu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…[ 25 ] Sulfonation is one of the chemical approaches for changing surface property where sulfuric acid is used to modify the surface morphology of PEEK through etching action. Sulfonation of PEEK has mostly been exploited for ion‐exchange membranes [ 26 ] used in fuel cell applications, [ 27 ] although a few recent studies have emerged on biomedical applications of sulfonated PEEK [3a,18e,28] . The sulfonation of mechanical dogbone and cylindrical bioactivity scaffold samples were performed by dipping them into concentrated (12 mol) sulfuric acid (H 2 SO 4 ) for 5 min (selected from literature) at room temperature followed by thorough (3×) rinsing with deionized (DI) water (see Figure ) .…”
Section: Methodsmentioning
confidence: 99%
“…[ 25 ] Sulfonation is one of the chemical approaches for changing surface property where sulfuric acid is used to modify the surface morphology of PEEK through etching action. Sulfonation of PEEK has mostly been exploited for ion‐exchange membranes [ 26 ] used in fuel cell applications, [ 27 ] although a few recent studies have emerged on biomedical applications of sulfonated PEEK [3a,18e,28] . The sulfonation of mechanical dogbone and cylindrical bioactivity scaffold samples were performed by dipping them into concentrated (12 mol) sulfuric acid (H 2 SO 4 ) for 5 min (selected from literature) at room temperature followed by thorough (3×) rinsing with deionized (DI) water (see Figure ) .…”
Section: Methodsmentioning
confidence: 99%
“…Since then, several materials have been investigated and not only pure metals were explored but also metals, ceramics modified with biocompatible coatings, and polymers. Some examples include calcium phosphate and hydroxyapatite (HA) [ 3 , 4 , 5 , 6 ]; some metal alloys, such as nickel-titanium (NiTi), stainless steel, and Vitallium (a cobalt-chrome alloy composed of 65% Co, 30% Cr, and 5% Mo) [ 7 ]; ceramic cements like alumina (Al 2 O 3 ), spinel (MgAl 2 O 4 ) and zirconia (ZrO 2 ) [ 4 ]; and polymers such as sulfonated poly(ether-ether-ketone) (PEEK), poly(methylmethacrylate) (PMMA), and polylactic acid (PLA) [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…It can be seen that the 1015 cm À1 in the infrared spectrum of the SPEEK is the stretching vibration absorption peak of the S k O bond in -SO 3 H. The absorption peak at 707 cm À1 , is caused by the symmetric stretching vibration of the S-O-C bond, and it can be preliminarily determined that the SPEEK has successfully introduced the sulfonic acid group. 29 It is confirmed that the introduction of sulfonic acid group did not change the basic structure of PEEK, and PEEK has been successfully sulfonated. 30 Figure 2 shows the SEM image and energy spectrum (EDS) of PEEK and SPEEK.…”
Section: Microstructure Of Peek Speek and Pesmentioning
confidence: 70%